Preparation and characterization of periodic mesoporous organosilicas - Wang, Wenhui (University of Ottawa (Canada), 2004)
Periodic mesoporous organosilicates (PMOs) are hybrid materials whose framework is comprised of alternating organic and inorganic species. These materials are prepared via supramolecular templating assembly using bridged silsesquioxanes (RO)3Si-R'-Si(OR) 3 as precursors, and surfactants as templates. This thesis is devoted to the preparation and characterization of phenyl- and ethenylene-bridged PMOs. The phenylene-containing precursor (bis(triethoxysilyl)benzene was synthesized by Barbier-Grignard reaction, whereas the ethylene derivative bis(triethoxysilyl)ethylene was prepared by self-metathesis reaction. They were characterized by 1H and 13C NMR, and mass spectrometry. The corresponding mesoporous materials were prepared using these precursors in the presence of different types of surfactants including oligomeric alkyl polyethylene oxide, triblock polyalkylene oxide copolymer and alkyltrimethylammonium surfactants. To obtain highly ordered mesoporous organosilicates, different synthesis conditions were employed and optimized. All materials were characterized using XRD, TEM, SEM, nitrogen adsorption, 29Si and 13C solid state NMR. In addition, some post-synthesis reactions using these materials were investigated.
Keywords: Chemistry, Organic.